Bioelectrochemical Chain Elongation of Short‐Chain Fatty Acids Creates Steering Opportunities for Selective Formation of n‐Butyrate, n‐Valerate or n‐Caproate. Issue 29 (4th August 2020) - Raes, Sanne M. T.; Jourdin, Ludovic; Buisman, Cees J. N.; Strik, David P. B. T. B.
Abstract: Valorization of organic residual streams that produce short‐chain fatty acids (SCFA) require an energetic electron donor to form more valuable elongated products. By microbial electrosynthesis such electrons donor is supplied by an electrode. Here we show that bioelectrochemical chain elongation (BCE) of SCFA was steered to high selective product formation efficiencies depending on the supplied fatty acid. n‐ Butyrate, n‐ valerate, n‐ caproate were in different experimental conditions formed at respectively 94.1, 95.4 and 83.4% carbon‐based selectivity. The reactor microbiomes adapted to the new feeding conditions within a few days. Remarkably, propionate elongation appeared to be preferred over acetate elongation. Propionate elongation resulted in highly selective formation of the odd‐chain fatty acid n‐ valerate; this seems contradictory to ethanol chain elongation studies in which acetate is concurrently formed leading to straight fatty acids as by products. Abstract : Valorization of organic residual streams that produce short‐chain fatty acids require an energetic electron donor to form more valuable elongated products. By microbial electrosynthesis such electrons donor is supplied by an electrode. Bioelectrochemical chain elongation of short‐chain fatty acids was steered to high selective product formation efficiencies depending on the supplied fatty acid. n ‐Butyrate, n ‐valerate, n ‐caproate were in different experimental conditions formed at respectively 94.1, 95.4 and 83.4% carbon‐based selectivity.